Transcriptomic profiling of effects of emamectin benzoate on the pine wood nematode Bursaphelenchus xylophilus. Issue 2 (31st August 2019) - Lu, Feng; Guo, Kai; Chen, Anliang; Chen, Shani; Lin, Haiping; Zhou, Xiang
Abstract: BACKGROUND: Emamectin benzoate (EB) has recently been successfully applied as a trunk injection for preventative control of the pine wilt disease (PWD) caused by Bursaphelenchus xylophilus (Steiner & Buhrer) Nickle. Here, a whole‐organism transcriptomic analysis provides comprehensive insights into the adverse effects of EB on B. xylophilus . RESULTS: A large set of differentially expressed genes (DEGs) were found, demonstrating the antagonistic effects of EB on B. xylophilus embryonic and larval development, reproduction, nervous and motor systems, and pathogenesis. In toxicity assays with EB, the number of eggs laid, hatching rate, thrashing frequency, and developmental rate of B. xylophilus were significantly suppressed at low concentrations (0.1 μg mL −1 ). Moreover, the transcriptional changes validated by real‐time quantitative PCR showed downregulated transcript levels of the genes encoding pectate lyases, β‐1, 4‐endoglucanases, and upregulated the genes encoding glutamate‐gated chloride channel, γ‐aminobutyric acid type β receptor, uridine 5′‐diphospho‐glucuronosyl transferase, ATP‐binding cassette transporter. The potential responses of B. xylophilus to EB included the upregulation of several genes putatively contributing to oocyte protection, stem cell renewal, and xenobiotic degradation, implying the potential for drug resistance to develop. CONCLUSION: Our findings further our understanding of the effects of EB for managing the PWD and may help to improve the pesticide‐use strategies for controlling B. xylophilus . © 2019 Society of Chemical Industry Abstract : Our study provides comprehensive insights into the adverse effects of EB on the invasive pest pine wood nematode (PWN) based on a whole‐organism transcriptomic analysis and toxicity assays.